Monetary Theory According to Imam Al Maqrizi - Pramayanti, Dian Ikha; Janwari, Yadi; Jubaedah, Dedah (International Journal of Law Social Sciences and Management, 2024)
One of Al Maqrizi's important contributions is his understanding of the importance of stabilizing currency values. He observed that fluctuations in currency values could lead to economic instability and depress economic growth. Therefore, he expressed his strong view of the need to maintain currency stability through proper regulation. The approach used in this study is a juridical normative approach. This approach examines the problem of rules relating to the monetary concept of Imam Al-Maqrizi. In this study, the data collection method that researchers used was the documentation method, namely finding data about things or variables in the form of books, newspapers, journals, and so on. The technique used is content analysis or content review. The results of the research show that Al-Maqrizi's thinking about monetary is that the currency used by mankind is better in the form of gold and silver. According to Al-Maqrizi, there are two types of inflation, namely natural inflation and inflation caused by human error. According to Maqrizi, the way to prevent inflation is to manage monetary policy appropriately. In addition, Al Maqrizi also suggested that currency exchange be carried out in a balanced manner. Exchange of currency for gold or silver should be done below its true value to avoid causing price distortions and inflation. Maintaining the stability of currency exchange rates and maintaining balanced currency exchange is expected to help reduce inflation in Indonesia.